A PENGEMBANGAN MEDIA PEMBELAJARAN VISUAL BERBASIS TEKA-TEKI SILANG DALAM MENINGKATKAN MINAT BELAJAR SISWA - Lutfy Nur Rahmawati; M. Ngali Zainal Makmum; Nurul Aisyah (Al-Aulad: Journal of Islamic Primary Education, 2026)
Learning IPAS (Integrated Science and Social Studies) in elementary schools is often hampered by the lack of interactive media which results in low student learning interest. This study aims to develop crossword puzzle learning media and determine the level of media feasibility and student responses to its use in increasing student learning interest. The research method used is Research and Development (R&D) with the ADDIE. The research subjects were students of class third A MI Ma'arif 18 Trimurjo. Data collection techniques were carried out through documentation, interviews with class teachers and principals, validation questionnaires from material experts and media experts, and student response questionnaires. The results of the study showed that the developed crossword puzzle media obtained a feasibility percentage of (100%) from material experts and media experts with a very feasible category. Student responses to the use of crossword puzzle media also obtained a percentage (100%) with a very good category, which indicates that this media is very valid and feasible to increase student learning interest in science learning. The study results show that crossword puzzle are a viable alternative solution for science learning. The use of this creative medium has a positive impact on increasing student learning interest, making it a strategic choice for creating a more dynamic and enjoyable learning environment.